APPLICATION OF CASE TASKS IN THE ASSESSMENT OF PROFESSIONAL COMPETENCE OF A FUTURE TEACHER - Galiakberova , Аifinur; Grakhova, Svetlana; Zakharova, Irina (Revista Inclusiones, 2020)
The introduction of a new model of certification of teachers in Russian Federation, based on the implementation of the principles of the activity approach in pedagogical practice, as well as the requirements for applying professional actions in the course of pedagogical work, determines the problems of assessing the level of formation of professional competencies among graduates of pedagogical universities. To assess the pedagogical skills of students, it is necessary to determine (operationalize) those indicators that would reveal the compliance of the performed actions with the requirements of the Federal State Educational Standards and the Professional Teacher Standard.